HLA class II antigen-processing pathway in tumors: molecular defects and clinical relevance - Seliger, Barbara; Kloor, Matthias; Ferrone, Soldano (OncoImmunology, 2017)
The human leukocyte antigen (HLA) class II antigen-processing machinery (APM) presents to cognate CD4+ T-cells antigenic peptides mainly generated from exogeneous proteins in the endocytic compartment. These CD4+ T cells exert helper function, but may also act as effector cells, thereby recognizing HLA class II antigen-expressing tumor cells. Thus, HLA class II antigen expression by tumor cells influences the tumor antigen (TA)-specific immune responses and, depending on the cancer type, the clinical course of the disease. Many types of human cancers express HLA class II antigens, although with marked differences in their frequency. Some types of cancer lack HLA class II antigen expression, which could be due to structural defects or deregulation affecting different components of the complex HLA class II APM and/or from lack of cytokine(s) in the tumor microenvironment. In this review, we have summarized the information about HLA class II antigen distribution in normal tissues, the structural organization of the HLA class II APM, their expression and regulation in malignant cells, the defects, which have been identified in malignant cells, and their functional and clinical relevance.